A práxis artística e expressiva do ensino da cor nas artes visuais com a contribuição da pedagogia histórico-crítica no ensino médio - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This dissertation is part of the Teaching and Learning research line of the Graduate Program in Education-PPGE/UEPG/PR. Its object of research is the artistic praxis in the teaching of Color in the Visual Arts with the contribution of Historical-Critical Pedagogy, and is justified by the tenuous appropriation of theoretical knowledge and chromatic practice in the Visual Arts by students of the 1st (first) year of Teaching Technical Medium, even though this knowledge is contemplated in several years of Basic Education, reflecting in their perceptions and artistic expressions as a social practice. The research sought to answer the following problem: How is the teaching of Color in the artistic and expressive praxis in the Visual Arts with the contribution of Historical-Critical Pedagogy in the 1st year of High School? And it has the general objective of developing an artistic and expressive praxis with the teaching of Color in the Visual Arts, contextualized and problematized in the learning of students in the 1st (first) year of High School, with the contribution of Historical-Critical Pedagogy. The theoretical framework is grounded and supported by theoretical and practical knowledge predominantly in the foundations of authors such as: Pedrosa (1982, 2006); Silveira (2011); Arhneim (2000); Spiller (1961); Barros (2006); Farina (1982); Guimarães (2000), Saviani (1986; 2007; 2011; 2015); Vazquez (1965, 1977); Lukacs (1963, 1968, 2011); Saviani and Duarte (2012); Goethe (1993), Carr and Kemmis (1988); Duarte (2008; 2013; 2016); Vygotsky (1999); Nunes (2004; 2006; 2009; Wick (1989) and Thiollent (2003;2007). The collaborators of the research were a group of 1st year of High School, composed of 29 students. The research approach was qualitative, with methodological design of action-research and pedagogical intervention in artistic praxis in the teaching of Color, during Art classes at Colégio Estadual Dr. Epaminondas Novaes Ribas in the city of Ponta Grossa/ Paraná. The research is organized into 4 (four) chapters. In this investigation , instruments and data materials were used, an initial questionnaire for the previous knowledge of the participating students about Color knowledge, participant observation, artistic productions of the students and their portfolios, the researcher's portfolio. With the outcome of the research, it can be concluded that from the initial questionnaire, most of the students participating in the research had not apprehended the conceptions of Color in artistic, expressive and social praxis, presenting superficial definitions and conceptions, or common sense. The result of the research, with the mediation of the researcher in the multidisciplinary scope, obtained a relevant and surprising artistic praxis, proven in the students' productions and narratives, as well as in the transformation of previous concepts to scientific concepts about Color, such as accumulated and systematized historical knowledge, prepared at school in the discipline of Art, as a social, cultural, artistic and scientific phenomenon, in artistic practice, with the contribution of Historical-Critical Pedagogy.
Keywords: Ensino da cor; Pedagogia Histórico-Crítica na Arte; Práxis Artística no Ensino Médio; Produções artísticas; Color teaching; Historical-Critical Pedagogy in Art; Praxis in High School; Artistic productions; CNPQ::CIENCIAS HUMANAS::EDUCACAO